The World Book student discovery encyclopedia vol. 6 - "World Book Inc." (,The World Book Inc. Chicago, 2000)
"A 13-volume, illustrated, A-Z general reference encyclopedia for students with high interest, low reading levels, providing traditional features of adult reference works, plus activities, atlas of world maps, special articles, and cumulative index"--Provided by publisher